An indigenous book keeps the bribri people’s identity - Vargas Mena, Emilio (2026)
This is a review of the trilingual book by Alí García Segura, Ditsö rukuö. Identity of the seeds: learning from nature, edited by the International Union for Conservation of Nature (IUCN), in Gland, Switzerland, in 2016. The book has 86 pages and 8 color illustrations by the artist Francini Gómez. Its ISBN is 978-2-8317-1824-8.